Pielgrzymki religijne: drogi rozwoju z potencjału światłości: Przyczynek do systemu René Girarda - Wójtowicz, Andrzej (Przegla̜d religioznawczy, 2013)
A pilgrimage is a topos of culture. It sets its topics. It organizes its discourses, genres of literature, motives of history, anthropology of religion and cultural anthropology. Within sociology of religion, ethnology and ethnography it is a topic of historical, empirical and systematic studies, and an object of comparative studies. Accordingly in comparative study of religion in a special manner. In general history, since the works of the Annales school, it points out questions on visions and concepts of man within the socio-historical structures, cultural boundaries, époques, and the phases of their transformations. Hinduism, Islam, Buddhism, Roman Catholicism, and Judaism rule over religiosity of pilgrimages, territorial religiosity, religious categorization of space and time, systems of religious classification of basic units of relevance. The study of religion and sociological examination finds an anthropological trait of the pilgrimage: reclaiming soil in the light of forces creating them. Its presentation and analysis is the addition of the René Girard's system.